2021
DOI: 10.1186/s41039-021-00158-8
|View full text |Cite
|
Sign up to set email alerts
|

The educational power of humor on student engagement in online learning environments

Abstract: The primary goal of the study is to investigate the effect of the usage of humor on behavioral, emotional, and cognitive engagement in online learning. Humorous elements were integrated into the online learning components. The mixed-method study was conducted over 14 weeks with the participation of 74 university students in an online university course. As a result, elements of humor can be integrated into materials for attention grabbing, recalling, feedback, and humor breaks. A diversity of humorous elements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
2
27
0
2
Order By: Relevance
“…Research findings by Aguilera-Hermida (2020) revealed that attitude, motivation, self-efficacy and technology use play an important role in students' cognitive engagement and academic performance. In the study conducted by Erdoğdu and Çakıroğlu (2021), the positive effect of humour elements in online materials on increasing behavioural, cognitive and emotional engagement was observed. In the study conducted by Petillion and McNeil (2020), open communication and flexible teaching and assessment methods are recommended to ensure student engagement.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 96%
“…Research findings by Aguilera-Hermida (2020) revealed that attitude, motivation, self-efficacy and technology use play an important role in students' cognitive engagement and academic performance. In the study conducted by Erdoğdu and Çakıroğlu (2021), the positive effect of humour elements in online materials on increasing behavioural, cognitive and emotional engagement was observed. In the study conducted by Petillion and McNeil (2020), open communication and flexible teaching and assessment methods are recommended to ensure student engagement.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 96%
“…В ряде недавних исследований изучается взаимосвязь между онлайн-образованием и уровнем студенческой вовлеченности с акцентом на разработке учебных курсов [Tualaulelei et al, 2021], через призму теории детерминации [Chiu, 2021] и даже с точки зрения влияния юмора [Erdoğdu, Çakıroğlu, 2021]. Очевидно, что цифровые технологии, инструменты и платформы имеют большой потенциал как средства поддержки дистанционного обучения [García-Morales, Garrido-Moreno, Martín-Rojas, 2021].…”
Section: аннотация ключевые словаunclassified
“…Estas evidencias científicas han ayudado a fortalecer y dar soporte directo a la Teoría del Procesamiento del Humor Instructivo (IHPT) propuesta por Wanzer et al (2010), y recientemente validada por Tsukawaki e Imura (2020). Esta teoría ha sido mencionada y utilizada en la introducción/marco teórico del 24% de las investigaciones publicadas sobre el humor y el aprendizaje Goodboy et al, 2015;Machlev y Karlin, 2016;Bolkan et al, 2018;Tsukawaki e Imura, 2020;Erdoğdu y Çakıroğlu, 2021).…”
Section: Relación Entre El Humor Y El Aprendizajeunclassified